Trust and the Welfare State: the Twin Peaks Curve. (12th January 2016) - Algan, Yann; Cahuc, Pierre; Sangnier, Marc
Abstract : We show the existence of a twin peaks relation between trust and the size of the welfare state that stems from two opposing forces. Uncivic people support large welfare states because they expect to benefit from them without bearing their costs. But civic individuals support generous benefits and high taxes only when they are surrounded by trustworthy individuals. We provide empirical evidence for these behaviours and this twin peaks relation in the OECD countries.